Effects of the Er, Cr:YSGG laser irradiation on dentin bond strength - Piccioni, M. A.R.V. [UNESP]; Neves, T. P.C. [UNESP]; Kubo, C. S. [UNESP]; Saad, J. R.C. [UNESP]; Campos, E. A. [UNESP] (IOP Publishing, 2016)
The aim of this study is to evaluate the influence of Er,Cr:YSGG laser irradiation and bur on the bond strength of different single step self-etch adhesive systems in normal and artificially hypermineralized dentin. In total, 112 human molars were selected. The specimens were randomly divided into two different groups according to the type of dentin. The teeth from each group were randomly divided into two subgroups according to the adhesive system used: Clearfil S3 Bond and Optibond All in One. Each subgroup received different treatments: (1) conditioning conventional; (2) conditioning of the dentin surface with Er,Cr:YSGG + application of the adhesive system; (3) 'surface roughening' dentin with 3098 diamond bur + application of the adhesive system. The matrices were positioned, filled with composite resin and photoactivated for 40 s. After a storage period of 24 h in a humid environment, the specimens were submitted to microshear bond strength testing. Subsequently, the fracture pattern of each sample was determined. One specimen per group was prepared in order to evaluate the interface and/or appearance of resin tags. The data of the microshear bond strength (μSBS) were analyzed by two-way ANOVA and Tukey's (p <0.05). In the hypermineralized dentin, there was no significant statistical difference between all the treatments employed, enhancing the option of employing single step self-etch adhesives in dentin sclerotic.
Keywords: dentin; laser; single step self-etch adhesives